Intracranial inflammatory pseudotumour related to IgG4: A very rare case - Ghassen Gader; Meissa Hamza; Ftima Zarraa; Ines Chelly; Ihsen Zammel; Mouna Rkhami; Mohamed Badri (Babol University of Medical Sciences, 2024)
Background: Intracranial inflammatory pseudotumours (IPT) are rare entities that frequently lead to misdiagnosis with malignant lesions. The identification of these lesions is difficult, but important to avoid inadvertent iatrogenicity and to adjust therapeutic protocols. Case Presentation: We report the case of a 30-year-old man who presented a single tonic-clonic seizure. Brain imaging showed a right frontal lesion with intra and extra axial components. Facing the radiologic presentation, a brain tumor was suspected, thus the patient underwent surgery. Pathological exam concluded to a plasma cell granuloma. A whole-body CT-scan showed only a thoracic aortitis. Complete blood work studies came back negative. The patient was also tested for an array of antibodies among which antinuclear antibodies were positive (blood level superior to 1/100). CSF evaluation revealed clear fluid with normal glucose concentration, normal protein levels and lymphocytic pleocytosis. Finally, IgG-4 plasma levels were elevated which led to the diagnosis of an IgG4-RD. The patient was put under prednisolone with a favorable outcome. Conclusion: IPT have several etiologies, among which IgG4 related disease may be one of the less known as only 2 cases have previously been reported. Herein, we report a new case of a young man who presented for seizures related to an intracranial lesion of an IgG4 related disease. The challenge is to suspect such conditions to avoid unnecessary surgeries.